Regional policy networks: IFPRI's experience with decentralization - Paarlberg, Robert L. (International Food Policy Research Institute, 2005)
IFPRI, traditionally a centralized development organization, is now embracing networks as one institutional strategy to achieve “regional decentralization.” Since 1999 IFPRI has developed and operated two formal regional networks, in East Africa and South Asia, and additional regional networks have been envisioned for Southern Africa and Central America. IFPRI is also decentralizing some of its work on a bilateral basis within individual countries without reliance on regional networks. This paper conceptualizes, maps out, and assesses IFPRI’s various decentralization initiatives.